Characteristics and temporal evolution of particulate emissions from a ship diesel engine. (1st October 2015) - Mueller, Laarnie; Jakobi, Gert; Czech, Hendryk; Stengel, Benjamin; Orasche, Juergen; Arteaga-Salas, Jose M.; Karg, Erwin; Elsasser, Michael; Sippula, Olli; Streibel, Thorsten; Slowik, Jay G.; Prevot, Andre S.H.; et al.
Abstract : Graphical abstract: Highlights: Marine sector is required to reduce particulate emission by using lower FSC. Medium speed engine with fuel switching capability for HFO and DF was used. Comprehensive characterization of emissions at different engine settings. Correlations of gaseous emissions with particulate emissions. Ship particulate emission can be reduced also by engine settings. Abstract: Due to current and upcoming regulations to address the adverse impacts of particulate matter (PM) from shipping emissions, the maritime sector is required to find energy-efficient ways to comply mainly by using low fuel sulfur content (FSC) in regulated seas. We studied the PM emission from a research ship diesel engine with fuel switching capability, optimized for HFO used at cruising, operated at representative engine loads resulting to varying excess O2 emission which was an indirect measurement of air–fuel mixture ( λ ), using heavy fuel oil (HFO, 1.6 S (%m)) and diesel fuel (DF, <0.001 S (%m)). We determined the characteristics and temporal evolution of the PM by using the High Resolution Time-of-Flight Aerosol Mass Spectrometry (HR-ToF-AMS) in combination with aethalometer, particle sizers, online gas phase, and filter measurements. The average emission factors were higher for HFO than for DF with relative percent differences of ∼200, ∼180, ∼150, and ∼145 for SO4 2 −, inorganic elements, organic matter (OM), and PM2.5, respectively, while that for black carbon (BC) was similar for both fuels. The difference between HFO and DF in terms of carbonaceous emissions was higher at 100% and 25% than at 75% and 50% engine loads. The exhaust temperature ( T ) decreased with increasing λ leading to the enhanced emission of OM in HFO and reduced OM and BC emission in DF. Contributions of hydrocarbons and oxygenated hydrocarbons increased with λ for HFO and decreased with DF. Gas phase total hydrocarbon (THC) was well correlated with BC only for HFO and OM and BC for DF. Overall, using a lower FSC reduced average PM emissions, however, engine load, and λ were strongly linked to the characteristics and temporal evolution of major PM emissions. The information in this study may help the marine sector and policy-making process in evaluating and designing future solutions for shipping emission regulations and diagnostics.